EFFECT OF PROBIOTICS ON GROWTH PERFORMANCE OF COMMON CARP CYPRINUS CARPIO VAR COMMUNIS - P. SIVAKUMAR; M.R. RAJAN; P. RAMACHANDRAN (International Journal of Pharma and Bio Sciences, 2014)
The present study deals with the isolation and identification of intestinal bacteria from Common carp Cyprinus carpio. and its effect on growth performance. Six experimental feeds such as Fl control (without probiotics), F2 (1ml of Proteus spp.), F3 (2ml of Proteus spp.), F4 (3ml Proteus spp.), F5 (4 ml of Proteus spp.), and F6 (1ml of yeast). Where prepared by using fish meal, Ground nut oil cake, wheat flour and tapioca. Fish were fed with the feeds at a rate of 4% of live body weight. And reared for a period of 30 days. Growth performance such as condition factor, FC, FCE, FCR, Growth, PG, RGR, Assimilation, Metabolism, GGE, and NGE, were calculated, after 30 days. Where ANOVA was studied FC, Growth, GGE and NGE. The results showed that growth parameters such as Feed Consumption, Feed Conversion Efficiency, Feed Conversion Ratio, Growth, Percentage Growth, Relative Growth Rate, Assimilation, Metabolism, Gross Growth Efficiency, Net Growth Efficiency was higher in F5 containing 4 ml of Proteus spp. and lower in F1 control (without probiotics)